Architectural Photographers Sourcebook. (Florida, United States : Sandow Media Corporation, 2007)
Architectural Photographers Sourcebook showcases a portfolio of some of the leading architectural photographers working today and their uncanny ability to breathe life into the skin and skeleton of buildings, articulating architectural intent with a play of light and shadow. Meet the photographers behind the stirring pictures and learn what inspires them.
Lewis Kennedy -- De Shields-Marley -- Mert Carpenter --Paul Jonason -- Peter Sellar -- McCory James -- Steve Mundinger -- Crystal Shafer -- Scott DW Smith -- Zach Wear -- Robert Benson -- John kane -- Carl Vernlund -- Maxwell Mackenzie -- Jeff Herbert -- Al Audleman -- Jan Johannes -- Shaw Mccutcheon -- Louis Novick -- Neil Rashba -- Antony Rieck -- Scott B. Smith -- Bill Wisser -- Reis Birdwhistell -- Lauren Rubinstein -- David Schilling -- Brian Bookwalter -- Jason Boyer -- James Moses -- John Spaulding -- Scott Dorrance -- Wiliam Taylor -- Thibault Jeanson -- Sean Busher -- Steven Paul Whitsitt -- Brad Feinknopf -- Matt Silk -- Jan Barfield -- Jay Brousseau -- Dan Ham -- Doug Handel -- Terry Manning -- David Sabal -- Ad Imagery -- William Milner -- Sonny Odom -- Thomas Bliss -- Roger Turk -- Eric Oxendorf -- Phil Weston.
Keywords: ARCHITECTURAL PHOTOGRAPHY